Adequacy of a compartment model for CMRO(2) quantitation using (15)O-labeled oxygen and PET: a clearance measurement of (15)O-radioactivity following intracarotid bolus injection of (15)O-labeled oxyhemoglobin on Macaca fascicularis - Iida, Hidehiro (Nature Publishing Group, 2014)
We aimed at evaluating the adequacy of the commonly employed compartmental model for quantitation of cerebral metabolic rate of oxygen (CMRO(2)) using (15)O-labeled oxygen ((15)O(2)) and positron emission tomography (PET). Sequential PET imaging was carried out on monkeys following slow bolus injection of blood samples containing (15)O(2)–oxyhemoglobin ((15)O(2)–Hb), (15)O-labeled water (H(2)(15)O), and C(15)O-labeled hemoglobin (C(15)O–Hb) into the internal carotid artery (ICA). Clearance slopes were assessed in the middle cerebral artery territory of the injected hemisphere. The time–activity curves were bi-exponential for both (15)O(2)–Hb and H(2)(15)O. Single exponential fitting to the early (5 to 40 seconds) and late (80 to 240 seconds) periods after the peak was performed and the (15)O(2)–Hb and H(2)(15)O results were compared. It was found that a significant difference between the clearance rates of the (15)O(2)–Hb and H(2)(15)O injections is unlikely, which supports the mathematical model that is widely used to describe the kinetics of (15)O(2)–Hb and H(2)(15)O in cerebral tissues and is the basis of recent approaches to simultaneously assess CMRO(2) and cerebral blood flow in a single PET session. However, it should be noted that more data are necessary to unequivocally confirm the result.